Ordered Mesoporous Materials - Zhao, Dongyuan; Zhou, Wuzhong, 1963-; Wan, Ying (Weinheim : Wiley-VCH, 2013)
The first book devoted to all aspects and types of mesoporous materials describes, in an in-depth and systematic manner, the step-by-step synthesis, synthesis mechanism, characterization, morphology control, hybridization, and applications of mesoporous molecular sieves. In so doing, it covers silicates, metal-doped silicates, non-silicates, and organic-inorganic hybrids. While the emphasis is on synthesis, the leading expert authors also discuss characterization and applications ranging from catalysis and biochemistry to optics and the use of these materials as templates for nanomaterial synthesis. Both the fundamentals as well as the latest research results are covered, ensuring this monograph serves as a handy reference for researchers as well as newcomers to the field.
Synthesis Approach of Mesoporous Molecular Sieves -- Mechanisms for Formation of Mesoporous Materials -- Structural Characterization Methods -- Representative Mesoporous Silica Molecular Sieves -- Doping in Mesoporous Molecular Sieves -- Morphology Control -- Mesoporous Nonsilica Materials -- Organic Group Functionalized Mesoporous Silicas -- Applications of Mesoporous Molecular Sieves.
Includes bibliographical references and index.
Text in English.
Print version record.
Keywords: Mesoporous materials; TECHNOLOGY & ENGINEERING -- Material Science; Mesoporous materials; Electronic books; Electronic books; Electronic books